2020
DOI: 10.5348/100083z06ds2020cr
|View full text |Cite
|
Sign up to set email alerts
|

“One in a million”: A case of a very early onset schizophrenia

Abstract: Introduction: Very early onset schizophrenia (VEOS), psychosis prior to age 13, is rare with an incidence of less than 0.04%. Its clinical presentation, course, and outcome differ from early onset (ages 13–18) and adult onset (ages 18 and up) schizophrenia. It is associated with poor response to treatment, poorer prognosis, and multiple hospitalizations. Early identification and intervention has shown to improve overall functioning. Case Report: We present a case of a 12-year-old female with significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…VEOS is a rare psychiatric illness with an incidence of less than 0.04% [8]. Patients with VEOS face significant barriers to receiving the care that they require as they get older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEOS is a rare psychiatric illness with an incidence of less than 0.04% [8]. Patients with VEOS face significant barriers to receiving the care that they require as they get older.…”
Section: Discussionmentioning
confidence: 99%
“…They found that acute onset of symptoms, higher IQ, fewer negative symptoms at the onset of the illness, and right medication adherence were all associated with remission and better outcomes for their patients [9]. The need to provide psychosocial supports to patients with VEOS and their families are essential for overall improvement in functioning [8]. One hurdle is that many patients do not achieve a level of functioning to live and work independently, and they often require very long-term treatment.…”
Section: Discussionmentioning
confidence: 99%